Determining the motivations of licensed librarians for pursuing continuing professional development - Montero, Genesis DC (School of Library and Information Studies, University of the Philippines Diliman, 2017)
This study intended to find out the motivating factors of librarians to pursue Continuing Professional Development. The study also sought the general opinion of librarians and the factors that hinder them from pursuing Continuing Professional Development. The findings can be used to strategically make adjustments to the CPD programs offered to suit the interests and needs of the librarians. The researcher conducted a focused group discussion to gather data in which six librarians from different library types participated. It was found that the librarians were already intrisically motivated to learn and pursue CPD. This arose from various needs but significantly from cognitive needs and the need for achievement. The hindrances from pursuing CPD rooted from the lack of time and human resource. The perceived limitation to the librarians' autonomy with regards to career growth because of the law was also a hindrance.